2017
DOI: 10.18001/trs.3.2(suppl1).4
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Behavior and Smoke Constituents from Cigarillos and Little Cigars

Abstract: Objective-Although most cigarillos and little cigars smokers also smoke cigarettes (dual use), there are few studies comparing toxicant exposure and smoking behavior in cigars and cigarettes.Methods-Two groups of dual users smoked their usual brand of cigarette and either a Winchester unflavored little cigar (N = 21) or a Black & Mild cigarillo (N = 23). Acute exposure of nicotine and exhaled carbon monoxide (CO) and puffing topography parameters were collected. Individual cigar puffing data were used to machi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…65 Reports have indicated that cigar smoke in general is as toxic as cigarette smoke. 4 Our data indicate that under more intense machine smoking regimens, which still may underestimate human smoking behaviors, 66 yields of toxic HPHCs from little cigars in particular are 1–4X higher than those found in a representative reference cigarette. In addition, the delivery of nicotine at levels like those found in the reference cigarette indicate the addictive potential and appeal of little cigars.…”
Section: Discussionmentioning
confidence: 75%
“…65 Reports have indicated that cigar smoke in general is as toxic as cigarette smoke. 4 Our data indicate that under more intense machine smoking regimens, which still may underestimate human smoking behaviors, 66 yields of toxic HPHCs from little cigars in particular are 1–4X higher than those found in a representative reference cigarette. In addition, the delivery of nicotine at levels like those found in the reference cigarette indicate the addictive potential and appeal of little cigars.…”
Section: Discussionmentioning
confidence: 75%
“…The report by Koszowski et al 40 illustrates another purpose of the studies were to compare mainstream smoke constituents in the cigar products. That objective dictated that we choose a single referent prototypical cigar product for each of the groups.…”
Section: Discussionmentioning
confidence: 99%
“…Using data from the national, longitudinal Population Assessment of Tobacco and Health (PATH) Study, we assessed how cigar package quantity relates to price and cigar use over two time-points for filtered cigars, cigarillos, and large cigars. Each cigar type was examined separately because of potential differences in user characteristics, products, use behaviors (e.g., puffing, inhaling, use frequency), and how the products are sold [24–26]. We examined whether, compared to longer-term users, people who recently started using cigars purchased smaller quantity packages, and whether buying larger, rather than smaller, packages predicted increasing one’s cigar smoking over time, continuing to smoke each cigar type, and continuing or starting to smoke a different cigar type or cigarettes.…”
Section: Introductionmentioning
confidence: 99%